"Balle-Balle, Balle-Balle": Fashion – British bhangra style*. Issue 4 (1st October 2016) - Dudrah, Rajinder
ABSTRACT: This article explores the fashion and style politics that can be found in the development of British bhangra music: a post-war song and dance genre that fuses elements of Punjabi lyrics and traditional South Asian instruments with global music including pop, disco, RNB, reggae, dance, grime and Bollywood. Existing research on this genre has primarily been presented in terms of musical and lyrical analysis as well as the politics of identity formation for its British Asian artists and audiences. Contributing to this work but also developing a hitherto unexplored area, the fashion and style politics of dress in British bhangra is analysed to consider socio-cultural possibilities for exploring British Asian bodies. The article uses a cross-disciplinary approach from Media and Cultural Studies and Fashion Studies to read fashion in British bhangra music videos, album cover sleeve artwork, and in the memorabilia and visual archives from the "Soho Road to the Punjab" exhibition.